NUPR1 Silencing Induces Autophagy-Mediated Apoptosis in Multiple Myeloma Cells Through the PI3K/AKT/mTOR Pathway - Li, Anmao; Li, Xingxin; Chen, Xuanxin; Zeng, Chensi; Wang, Zuo; Li, Zhen; Chen, Jianbin (DNA and cell biology, 2020)
Nuclear protein 1 (NUPR1) is a stress-related small molecule and plays important roles in various tumors, including multiple myeloma (MM). Autophagy is essential for maintaining cellular homoeostasis in response to stress and, together with apoptosis, determines cell fate. Previous studies indicate that NUPR1 is involved in cancer progression of MM, but the underlying mechanisms have not been elucidated. In this study, we confirmed that NUPR1 and basal autophagy markers were highly expressed in the bone marrow of MM patients. The overexpression of NUPR1 was correlated with staging (both by Revised International Staging System [RISS] and Durie-Salmon [D-S] Staging System), levels of hemoglobin and calcium, and bone marrow plasma cell ratio in the MM patients. NUPR1 silencing reduced autophagy activities and induced apoptosis in U266 and RPMI 8226. We further observed a decrease in NUPR1 silencing-induced apoptosis in the presence of rapamycin, while an increase in apoptosis after chloroquine and 3-methyladenine treatment. Analysis of the mechanism indicated that PI3K/AKT/mTOR pathway was involved in autophagy-mediated apoptosis upon NUPR1 knockdown. In summary, our results demonstrate that NUPR1 silencing suppresses autophagy activities and induces autophagy-mediated apoptosis in MM cells through the PI3K/AKT/mTOR pathway, which exhibits potential as a treatment strategy for MM.